Effects of different methods of physiotherapy in individuals with cervicogenic headaches - Šližys, Tomas; Jazepčikienė, Edita (Slauga. Mokslas ir praktika, 2021)
Objective. To assess the effects of different physiotherapy methods in individuals with cervicogenic headache. Methods. 20 subjects with cervicogenic headaches have been studied. Subjects were randomized to two groups of 10 subjects. The first group of subjects underwent physiotherapy with post – isometric relaxation, the second group – physiotherapy in combination with vibration. Before and after the interventions, pain intensity, neck disability index, active cervical range of motion and neck muscle strength were evaluated in all subjects. Results. Physiotherapy reduces the intensity of pain (from strong and very strong to moderate intensity), improves neck function (from severe to moderate disability), increases active cervical range of motion by four to six degrees and increases neck muscle strength (p < 0,05). When comparing results between groups, no statistically significant difference in results were observed (p > 0,05). Conclusion: Complex physiotherapy in combination with post – isometric relaxation or vibration helps to improve the function of individual neck, increase active cervical range of motion and strength of muscle strength.